Work Stress Management Among Employees Of Pt. Pertamina (Persero) Pulau Baai Bengkulu - Ningsih, Marida Sari; Yusuarsono, Yusuarsono; Mirwansyah, Mirwansyah (Journal of Research in Social Science and Humanities, 2021)
This study aims to evaluate the influence of work stress and job satisfaction on employee performance at PT. Pertamina (Persero) Pulau Baai Bengkulu. Occupational stress is a critical managerial concern, particularly in large-scale organizations within the national energy sector, where intense workloads and responsibilities can lead to psychological disturbances and decreased productivity. Using a quantitative survey method, data were collected from 70 employees and analyzed through multiple linear regression. Partial testing results reveal that work stress does not significantly affect employee performance, suggesting that the perceived stress level remains within manageable limits. In contrast, job satisfaction shows a significant and positive effect, indicating that factors such as peer relationships, company policies, and employee recognition substantially influence individual performance outcomes. Simultaneous testing confirms that both work stress and job satisfaction jointly impact performance, although their overall contribution is relatively modest. These findings offer theoretical insights for human resource management literature and practical implications for organizations seeking to improve performance through structured stress management and satisfaction enhancement strategies. The study also underscores the need for regular monitoring of employee well-being indicators to ensure a productive and sustainable work environment.